Post-acute COVID-19 Syndrome Negatively Impacts Physical Function, Cognitive Function, Health-Related Quality of Life, and Participation. (January 2022) - Tabacof, Laura; Tosto-Mancuso, Jenna; Wood, Jamie; Cortes, Mar; Kontorovich, Amy; McCarthy, Dayna; Rizk, Dahlia; Rozanski, Gabriela; Breyman, Erica; Nasr, Leila; Kellner, Christopher; Herrera, Joseph E.; et al.
Abstract : Objective: This report describes persistent symptoms associated with post-acute COVID-19 syndrome (PACS) and the impact of these symptoms on physical function, cognitive function, health-related quality of life, and participation. Design: This study used a cross-sectional observational study design. Patients attending Mount Sinai's post-acute COVID-19 syndrome clinic completed surveys containing patient-reported outcomes. Results: A total of 156 patients completed the survey, at a median (range) time of 351 days (82–457 days) after COVID-19 infection. All patients were prevaccination. The most common persistent symptoms reported were fatigue ( n = 128, 82%), brain fog ( n = 105, 67%), and headache ( n = 94, 60%). The most common triggers of symptom exacerbation were physical exertion ( n = 134, 86%), stress ( n = 107, 69%), and dehydration ( n = 77, 49%). Increased levels of fatigue (Fatigue Severity Scale) and dyspnea (Medical Research Council) were reported, alongside reductions in levels of regularly completed physical activity. Ninety-eight patients (63%) scored for at least mild cognitive impairment (Neuro-Qol), and the domain of the EuroQol: 5 dimension, 5 level most impacted was Self-care, Anxiety/Depression and Usual Activities. Conclusions: Persistent symptoms associated with post-acute COVID-19 syndrome seem to impact physical and cognitive function, health-related quality of life, and participation in society. More research is needed to further clarify the relationship between COVID-19 infection and post-acute COVID-19 syndrome symptoms, the underlying mechanisms, and treatment options. Abstract : Supplemental digital content is available in the text.